MILLENIAL APPROACH USAGE TO IMPROVE SPEAKING SKILL - Permadi, Rudi (HASBUNA : Jurnal Pendidikan Islam, 2022)
Speaking skill is essential capability that must be mastered by the students with two consideration factors. Inward looking factor defines that speaking skill will involve and support their readiness in academic atmosphere such as presentation and oral test. Outward looking factor drives the student encountering their own problems after they graduate, such as job interview or society engaging. The research was carried out to recognize the influence of millennial approach on the students’ speaking achievement. Experiment with one group pre test and post test factorial design is played as research methodology. Speaking test ruled data collection. The number of sample is 60 students Islamic studies program IAI Tasikmalaya academic year 2021/2022. Random sampling works as technique of taking the sample. Data calculation and analysis concluded that Asymp. Sig. (2-tailed) =0.000 less than Asymp. Sig. (2-tailed) < 0.05 explaining that H0 is rejected. It means that there is a significant effect of millennial approach on the students’ speaking skill.